The Effect of Andaliman Oil on Low Back Pain in Trimester III Pregnant Women - Purba, Netty Herawaty; Maisyaroh UP, Septi; Pakpahan, Yohana F (International Journal of Public Health Excellence (IJPHE), 2025)
Nearly 70% of expectant mothers experience back pain, which makes it difficult for them to do daily tasks, including sleeping. This study sought to determine how Andaliman Oil affected third-trimester pregnant women's low back pain. Using a one-group pretest-postest design, which is a pre-experimental with a pre-test (taken before treatment) and post-test (taken after treatment) in one group, this research approach employs quasi-experiments. Third Trimester Pregnant Women with back and waist pain made up the study's sample. The Modified Oswestry Low Back (ODI) is the tool used to evaluate back discomfort. The application of andaliman oil is carried out by continually applying it to the mother's back and waist until the respondent has the sensation for fifteen minutes. After that, the mother is given a post-instrument to gauge the impact of andaliman oil on her pain levels. According to the findings of statistical testing, there was a decrease in back pain and a decrease in dysmenorrhea, with an average of 15.50. Additionally, a significant difference between the pre- and post-intervention periods is indicated by a p-value of less than 0.05. Additionally, the Z min value = -0.632 is found, indicating that longer and more frequent use of andaliman oil can lessen back discomfort in pregnant women in Third Trimester.